Bank fraud : exposing the hidden threat to financial institutions - Gup, Benton E. (Rolling Meadows, Ill. : Bankers Pub. Co., 1990)
Describes how banks can be harmed by embezzlement and fraud committed by both insiders and outsiders, and suggests ways for an alert management to prevent such crimes.
"No. 300"--T.p. verso.
Includes bibliographical references (p. 227-247).
rpm 05/09/2016
Loans
Keywords: Commercial crimes; Banks and banking; Fraud; Embezzlement; Bank management